The Impact of Price Up-limits and the IPO underpricing: Evidence from Chinses A-share Market - Gao, Yifan (2020)
High level of underpricing has been found in the stock markets in different countries. Chinses A-share market has the extremely high IPO underpricing compared to other countries. As China Securities Regulatory Commission launched the regulation of price up-limits on 2014, it is meaningful to examine whether this up-limits solve the problem of high IPO underpricing as well as the factors that cause the extremely high underpricing in the emerging stock market. The sample contains 1257 IPOs listed on Chinese A-share market from 2014 to 2019. Multiple regression model is used to examine the relation between independent variables and underpricing. Those independent variables include offering size, firm age, venture capital, state ownership, time lag, return on equity, lottery rate, turnover rate, underwriter reputation and issuing fees. The following conclusions are suggested in this study. First, the price up-limits regulation aggravates the degree of underpricing in Chinese A-share market. The result shows the average modified initial return of IPOs on Chinese A-share market is 287%, which is higher than that from 2010 to 2013. In terms of the factors impacted the IPO underpricing in China, this study find that the issuing fees and state ownership are highly positive to the level of underpricing whereas offering size, lottery rate, firm age and turnover rate is significantly negative to the level of underpricing. Moreover, return on equity and turnover rate is found to be negative to underpricing, but the relation is not significant. Last, there is no evidence suggests the involvement of venture capital and the underwriter reputation can influence IPO underpricing.